Taxonomy of Neotropical Trichomyia (Septemtrichomyia) Bravo (Diptera, Psychodidae, Trichomyiinae) with descriptions of five new species - Araújo, Maíra Xavier; Bravo, Freddy (Zootaxa, 2012)
Subgenus Septemtrichomyia Bravo of genus Trichomyia Haliday in Curtis was originally proposed to include four Neotropical species: T. botosaneanui Wagner, T. bou Bravo, T. cauga Bravo and T. mishi Bravo. Five new species are described for this subgenus: Trichomyia atlantica sp. nov., T. imarui sp. nov., T. jezeki sp. nov., T. amazonensis sp. nov. and T. sertaneja sp. nov.; five previously described species are included in Septemtrichomyia: T. dolichakis Quate, T. dolichopogon Alexander, Freitas & Quate, T. dolichothrix Quate, T. pedrabranquensis Bravo and T. sattelmairi Wagner & Masteller. A key to males of the 14 Neotropical species of Septemtrichomyia is presented.